GEOINFORMATION MANAGEMENT AS A MODERN APPROACH TO THE MANAGEMENT OF SPATIALLY-DISTRIBUTED SYSTEMS AND TERRITORIES - Istomin, Eugene P; Sokolov, Alexander G; Abramov, Valery M; Gogoberidze, George G; Popov, Nickolay N (International Multidisciplinary Scientific GeoConference SGEM, 2015)
We consider modern geoinformation approach to the management of spatially-distributed organizational-technical systems that is based on the attraction of spatial information. We examine basic aspects and complex models for support decision-making in geoinformation management: institutional, economic, technical, social, ecological. We present method of analysis for the territory characteristics and give the basic information arrays for solving practical management problems at different levels: the territory, the objects within the territory. While research we used decision theory, risk management approach, GIS technologies best practice. Contemporary technologies for the management of complex systems have to base on a system of factor conditions. In relation to spatially distributed systems within global reality it has to mind the process of globalization, the level of the world economic system development, the level of management technologies development and the usage of information networks of different scales with their capacities. Contemporary technologies for the management of complex systems have to base on a system of factor conditions. The system of factor conditions allow for a fresh look at the modern management system as a complex, geospatially distributed system of interaction between different subjects and objects of management that determines the appearance of the geoinformation management (GIM) phenomenon. (GIM) is management of territories and spatially distributed systems (SDS) with the active usage of geographic information systems (GIS) as the tools to support decision making. The general purpose of the GIM is to develop a set of alternative management decisions and to choice a best variant from them. The main elements of the GIM are correlated with normative-legal base blocks of planning, organization, motivation and control that are functioning with involving spatial information and the extensive using of the GIS. The result of the GIM is rational managerial decision on the basis of accepted criteria and the GIS as the tools to support decision making. In approach to GIM we structured geospace into some categories to highlight the interrelated space solution components: coordinate (geographic) space, factor space, event space, space of the states for the control, solution space. We used the platform https://www.researchgate.net/profile/Valery_Abramov2/?ev=hdr_xprf as a tool for scientific communication while research. The Ministry of education and science of Russia provides financial support for this research with the state order 2014/166.